OPTIMASI DISPOSISI SURAT DIGITAL MELALUI SISTEM INFORMASI BERBASIS WEB DI SMPN 1 BOJONEGARA - Muhamad Shiraj Al-Ayyubi; Sigit Auliana; Mochammad Darip (Universitas Majalengka, 2025)
Mail management at SMPN 1 Bojonegara is still done manually, causing delays in disposition, difficulty in searching for archives, and the risk of document loss. This study aims to design a web-based mail disposition information system to simplify and accelerate the administrative process. The system was developed using the Waterfall method through the stages of needs analysis, design, implementation, and testing. Analysis was carried out through observation and interviews, followed by design using UML, development with PHP (Laravel), and a MySQL database. The system was tested using the black-box method and showed that all features functioned as intended. As a result, letter recording, disposition, and archive searching can be done digitally and efficiently. This system also allows disposition to be carried out without the physical presence of the principal. Compared to previous research, this system is specifically designed for school needs and supports the recording of outgoing mail. Thus, this system supports a faster, neater, and safer correspondence process.